1991
DOI: 10.1179/imr.1991.36.1.187
|View full text |Cite
|
Sign up to set email alerts
|

Hot ductility of steels and its relationship to the problem of transverse cracking during continuous casting

Abstract: to which he has now returned.The hot ductility behaviour of steels in the temperature range 700-11 oooe when tested in tension at low strain rates is examined. Three distinct ranges of behaviour are displayed: (a) a high ductility, low temperature range which results from the presence of a large volume fraction of the more ductile ferrite phase; (b) a high temperature ductile region covering the range within which grain boundary particles are dissolved and boundaries are able to migrate so that any initiated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
516
1
10

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(539 citation statements)
references
References 69 publications
12
516
1
10
Order By: Relevance
“…[1][2][3] This correlates quite well with the observation that steels prone to transverse cracking exhibit very low ductilities (Ͻ20% reduction in area at fracture) at high temperatures. [3][4][5][6][7] With regard to transverse cracking, hot ductilities are usually determined by isothermal tensile test that includes melting and then cooling to the desired test temperature.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…[1][2][3] This correlates quite well with the observation that steels prone to transverse cracking exhibit very low ductilities (Ͻ20% reduction in area at fracture) at high temperatures. [3][4][5][6][7] With regard to transverse cracking, hot ductilities are usually determined by isothermal tensile test that includes melting and then cooling to the desired test temperature.…”
Section: Introductionsupporting
confidence: 73%
“…In general, the unbending operation, which takes place in the final stage of continuous casting process, coincides with this thermal region. [1][2][3][4][5][6][7] It is frequently reported that performing the unbending operation at the temperatures below or above the aforementioned thermal region has been moderately successful in improving the incidence of cracking in some problem grades because the temperature range of embrittlement has been avoided. 8) However, recent laboratory studies have shown that the thermal history itself has a pronounced effect on the hot ductility.…”
Section: Introductionmentioning
confidence: 99%
“…A Figura 9a foi adaptada para apresentar a localização dos 5 primeiros passes do desbaste do processo estudado, onde todos encontram-se dentro da zona de segurança. Mintz et al [13] …”
Section: Taxa De Deformaçãounclassified
“…Such strains are generated in the spray chambers or by the straightening. The latter one appears to result in crack formation if the surface temperature is too low, particularly in the range of 700-900 °C corresponding to the low temperature zone of low ductility [5,23,24].…”
Section: Evaluation Of the Risk Of Transverse Crackingmentioning
confidence: 99%
“…In [15], the link between segregation, low ductility, oscillation mark formation and transverse cracking is clearly underlined. Mintz [23,24] realized a large review on hot ductility of steels and its relationship to the problem of transverse cracking in continuous casting. He demonstrated the importance of four variables that mostly control hot ductility: the strain rate, the grain size, the precipitation and inclusion contents.…”
Section: Fig 1: Sketch Of Continuous Casting Processmentioning
confidence: 99%